The Dynamics Transformation of Public Policy Making in Indonesian Democracy - Andy Al Fatih (Indonesian Association for Public Administration (IAPA), 2020)
Public policies are purposed, basically, to solve public problems and for the sake of public welfare. They should, therefore, be made thoughtfully, implemented successfully, and give pleasant impacts to the target groups. This article is related to the dynamics transformation of public policy making in indonesian democracy. In centralistic political system, national government (executive body) controlled more essential public affairs. As the result, most public policies were much engineered and directed, mostly, to the needs of the in power. The tendentious public policies were abused for personal, group, and cronies’ interests of the in authority officials. The people were left behind, served as object of development, and stayed poor. It happened for decades. The people could not stand it any longer and struggled for a reformed government resulting in regional autonomy. Regional autonomy seems promising for the people’s prosperity. In this era, legislative body tends to control power. The people set hopes and wait for happiness. In fact, some members of parliament only show power. They control many walks of lives. They represent themselves rather than the people. They somewhat abuse power and make public policies for their own gains. The people are left behind again and still get disappointed. Here, a paradox occurs. The paradox must be sorted out well. The hot discussion begins. The actors blame to one another.